(untitled) (Global Journals of Research in Engineering, 2013)
The need of increasing the capacity of data transmitted within the fiber transmission links became a challenge for researcher. Even though optical fiber communication is the best communication system in transmitting high data rate but still users are hungry thus the researchers are pushing to get the highest bit rate. While the fiber channel may be capable of transmitting terabit-per-second data rates, no existing single communication system can make complete use of this speed. One of the main concerns in an optical network is the high cost of installation of components. The global network is made of a large submarine cable network that is expensive to modify and repair. An alternative solution to this is Wavelength Division Multiplexing (WDM) where each modulated signal is transmitted at an individual frequency, allowing full duplex data transmission. In WDM systems the available fiber bandwidth is divided into separate channels with each channel carrying one signal, thus increasing the overall data rate without increasing the number of fibers. The data rate of each channel can be limited, but with many channels the total data rate is considerably higher.WDM has not always been a popular choice. The invention of Erbium-doped fiber amplifiers (EDFA) with large bandwidth is largely responsible for popularizing this technique. In terms of multiwavelength signals, so long as the EDFA has enough pump energy available to it, it can amplify as many optical signals as can be multiplexed into its amplification band. These properties of EDFAs have enabled us to use Dense WDM (DWDM) technique, which uses denser channel spacing in order to achieve even higher bit rate. It is an interesting solution is to double the capacity of each fiber by using a duplexer. It is a system capable of duplex communication over a single fiber in contrast to two fibers required in the present scenario. The capacity can be further doubled by the application of DWDM techniques as opposed to conven